Developments of solid-phase microextraction fiber coatings for environmental pharmaceutical and personal care products analysis - Portillo Castillo, Omar Jassiel; Castro Ríos, Rocío; Chávez Montes, Abelardo; González Horta, Azucena C.; Cavazos Rocha, Norma Cecilia; Waksman de Torres, Noemí; Garza Tapia, Marsela (De Gruyter Brill, 2018)
Solid-phase microextraction (SPME) is a sample preparation technique with many applications that is being continuously developed. In this technique, the type of fiber coating plays a crucial role for extraction efficiency. Currently available commercial coatings have certain drawbacks that have been overcome by the development of new coatings based on novel materials; these have improved the efficiency of extraction, selectivity and stability of commercial coatings. Pharmaceutical and personal care products (PPCPs) are one of the most important groups of emerging contaminants; however, some studies suggest that these compounds can cause adverse health effects. No official monitoring protocols for these compounds are currently available, so the establishment of analytical methods that allow their determination in environmental samples is required. The complexity of environmental samples together with the low concentration levels of these compounds makes necessary the use of sample preparation techniques capable of removing interferences, as well as preconcentrated analytes, and SPME is a very promising alternative to achieve this. This review describes the recent developments in SPME with classical and novel coatings and its applications for PPCP determination in environmental samples.